HAZARD ANALYSIS AND CRITICAL CONTROL POINTS IMPLEMENTATION IN AMPLANG PROCESSING - Zulfatun Najah; Nia Ariani Putri; Taufik Hidayat; Zulmaneri Zulmaneri (Food ScienTech Journal, 2019)
Amplang is one of derivative products from fish in the form of crackers. It isindigenous food from Kalimantan. Amplang is produced by SMEs (Small and Medium Enterprises), which aremost of them still need to improve theirstandard processing method.  The quality standards of processing amplang in SMEs can be improved through implementation of quality assurance. The quality assurance was applied by identificationof hazards, assessing of risks, and control of hazards. The aim of this study was to analyze hazard of amplang production in the SME and to design the control of production process from purchasinguntilpackaging. The research method was survey research with data collection conducted by interviews, field observations, FGDs, and questionnaires. Based on observations, the SME’s quality control team needs to be established. Food hazards are divided into raw material and production process hazards. This review found nine kinds of hazard that necessary to be alerted in the amplang processing. These hazards can be divided into physical, chemical, and biological hazards. There are five processes that consider as critical control point that are purchasing, thawing, mixing, frying, draining, and packaging